Production of Thermoalkaliphilic Lipase from Geobacillus thermoleovorans DA2 and Application in Leather Industry. (3rd January 2016) - Abol Fotouh, Deyaa M.; Bayoumi, Reda A.; Hassan, Mohamed A.
Abstract : Thermophilic and alkaliphilic lipases are meeting a growing global attention as their increased importance in several industrial fields. Over 23 bacterial strains, novel strain with high lipolytic activity was isolated from Southern Sinai, Egypt, and it was identified as Geobacillus thermoleovorans DA2 using 16S rRNA as well as morphological and biochemical features. The lipase was produced in presence of fatty restaurant wastes as an inducing substrate. The optimized conditions for lipase production were recorded to be temperature 60°C, pH 10, and incubation time for 48 hrs. Enzymatic production increased when the organism was grown in a medium containing galactose as carbon source and ammonium phosphate as nitrogen source at concentrations of 1 and 0.5% (w/v), respectively. Moreover, the optimum conditions for lipase production such as substrate concentration, inoculum size, and agitation rate were found to be 10% (w/v), 4% (v/v), and 120 rpm, respectively. The TA lipase with Triton X-100 had the best degreasing agent by lowering the total lipid content to 2.6% as compared to kerosene (7.5%) or the sole crude enzyme (8.9%). It can be concluded that the chemical leather process can be substituted with TA lipase for boosting the quality of leather and reducing the environmental hazards.